Integrating genre-based approach in designing English syllabus for Islamic education study program - Maulida, De Lara Siti; Gunawan, Hevie Setia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Reaching decisions about what should be taught and how is highly crucial when designing a syllabus such as English syllabus regarding a number of issues. One of the issues is the demand to design a syllabus that meet with the students’ need. Thus, this paper aims to construct a prototype of an English syllabus for the Islamic Education Study Program as a response to the issue. In order to promote students’ writing skill, the developed prototype incorporates a genre-based approach in designing writing syllabus. This research employed Dick and Carey’s model of Research and Development in designing a prototype syllabus. The prototype of English syllabus design refers to the component of syllabus provided by SN-Dikti article 12 toward the syllabus components. The stages of GBA covers Building Knowledge of the Fields, Modelling, Independent Construction, Developing and Presenting the Task, and Analyzing and Evaluating the Written Text. The students are also familiarized with various genres to compose the text and relate it with Islamic values in daily life. The designed prototype syllabus then validated by expert judgements trough forum group discussion. The experts' feedback was used to refine and finalize the prototype syllabus.